Effectiveness of herbicide application with plant growth regulators and microfertilizer in late crops of winter wheat - Hutianskyi , R. (Quarantine and plant protection, 2023)
Goal. To establish the features of the formation of weed complex, yield and grain quality of winter wheat sown on the late sowing period, depending on the application of post-emergence herbicides, plant growth regulators and microfertilizers. Methods. Field, measuring and weighing, statistical, laboratory, analytical. results. According to the results of investigations in 2016—18, 30 species of weed plants were found in late crops of winter wheat: late spring grasses (3 species); early and late dicotyledonous (14 species); dicotyledonous wintering, winter and biennial (7 species); dicotyledonous perennials (6 species). In terms of quantity, late spring grasses weeds dominated (40.6%), and in terms of raw mass dicotyledonous perennials dominated (87.6%). Technical efficiency of tank mixture of anti-perennial herbicides Dekabrist 480 SL (0.15 l/ ha) + Gryzny, W.G. (15 g/ha) + Talant, surface-active substance (0.2 l/ha), when applied at the tillering stage (standard) against the total raw mass of dicot annual and perennial weeds was 96.7 and 69.2%, respectively. The low level of control of dicotyledonous perennial species by this tank mixture was associated with the partial regrowth of root-sprouting weeds, especially sow thistles, after the introduction of the specified herbicides, namely during the booting period. The application of plant growth regulators Emistym C, w.-a.s. (10 ml/ha) and Vermiiodis, w.s. (6.0 l/ha) at the booting stage, against the background of application of herbicides at the tillering stage, stimulated the growth of the raw weight of dicotyledonous perennials and the total raw weight of all weeds, compared to their application in a tank mixture with herbicides at the tillering stage. At the same time, these indicators, when applying microfertilizer Nanomix, s. (2.0 l/ha) in a tank mixture with herbicides at the tillering stage, were higher, compared to applying the preparation separately from herbicides at the booting stage. An increase in the level of raw mass of weeds against the background of the use of stimulating preparations led to a decrease in grain yield in most variants with these preparations, compared to the standard. No effect of the studied preparations on the protein content of the grain, as well as the germination energy and laboratory germination of the grown grain was found. Conclusions. The application of post-emergence herbicide compositions with plant growth regulators and microfertilizers in late crops of winter wheat stimulates the growth of the raw mass of weeds, which negatively affects the grain yield of the crop.